Pengaruh Persepsi Praktik HRM terhadap Kesuksesan Karir Melalui Kemampuan Kerja Serta Perilaku Kewargaan Organisasi (OCB) - Fasyariani, Nabila; Rojuaniah (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2024)
Every company needs quality human resources so that their work and work produce the best results. Therefore, the company must involve factors that can influence its attitude, namely with the HRM practices provided, in the end it will have a strong influence in increasing its capabilities including the behavior of organizational members to achieve individual career success. The purpose of this study was to see the effect of HRM practices associated with employees' perceptions of career success through employability and civic organizational behavior as mediating variables. This study used a purposive sampling approach involving 160 respondents who are permanent employees of the private banking sector in DKI Jakarta and Tangerang. Data were analyzed using Structural Equation Model (SEM) with SmartPLS 3.0. Some of the findings in this study are that perceptions of HRM practices have an effect on work ability and organizational citizenship behavior, while career success has no effect. Other findings prove that Work Ability and Organizational Citizen Behavior have a mediating role in the relationship between HRM Practices and Career Success. These results are expected to provide an overview of how a stage from start to towards a better career in order to be able to increase income and carry out self-development in the work environment. Keywords: Perceptions of HRM Practices, Employability, Organizational Citizenship Behavior, Career Success